مدى إمكانية تطبيق صيغ تمويل الخدمات والمنافع في المصارف الليبية = The extent of possibility of applying a mode of financing services and benefits in Libyan banks - A. Mohamed Barg Enab, Abubaker; Mohd Noor, Azman; Saleh, Abdulmajid Obaid Hasan (IIUM Press, International Islamic University Malaysia, 2019)
حددت مشكلة الدراسة بعدم قدرة المصارف الليبية علىمنح القروض الشخصية ؛بسالمارظنبه القانون رقم (1)لسنة 2013مالصادر عن مصرف ليبيا المركز يدتحنمللمصارف الليبية؛حيث منع القانون جميع المصارف الليبية التجارية الإقراض بفوائد ربوية،فيظل عدم وجود نشاط مصرفي إسلامي؛الأمر الذيدعا إلى إيجاد بديل مناسبللتمويل الشخصي. ويمكنأن يكون هذا البديل هو إيجاد صيغةتمويل الخدمات والمنافع معتمدا على الأحكام الشرعية. ولذا الهدف من هذا البحث هودراسة شروط و آلياتالعمل بصي غةتمويل الخدمات والمنافع، وإمكانيةتوظيفها كمصدر للتمويل الشخصيفيالمصارف الليبية.هذا،وقد اعتمدت الدراسة على المنهج الوصفي و التحليلي.و ةدعلىإةساردلاتلصوتنتائج،من أهمها:أنه يمكن تطبيق صيغةتمويل الخدمات والمنافع كمصدر للتمويل الشخصيلتلبية احتياجات العملاء ،كما تتمتع الصي غةبخصائص تؤهلهالأن تكون بديلاجيداللقروض الشخصية . ******************************************************************************* Law no. 1 of the year 2013 issued by the Central Bank of Libya has caused a challenge for Libyan banks because this law has prevented all Libyan commercial banks from providing personal loans with interest (riba) at a time when there was no existence of Islamic banking activities. This problem called for finding a suitable alternative for personal financing. An alternative would be the creation of financing services and benefits based on Shari`ah rules. Therefore, this research aims to study the conditions and work mechanisms for the mode of financing services and benefits and the possibility of employing it as a source of personal finance in Libyan banks. This research uses descriptive and analytical approaches. The study has arrived at a number of findings. The most important of them are: it is possible to implement the mode of financing services and benefits as a source of personal finance to meet the needs of customers, and this mode has the characteristics that qualify it to be a good alternative for personal loans.